Advanced Optimal For PV system coupled with PMSM - Salam Waley Shneen (Institute of Advanced Engineering and Science, 2016)
The main advantages of PMSM are high torque density, high efficiency and small size. Photovoltaic power generation system PV generation technology is treated as the most promising technology among renewable energies. Photovoltaic (PV) power generation system is a promising source of energy with great interest in clean and renewable energy sources. To use different control systems, like Classical PI Controller, Expert System Fuzzy Logic Controller and Optimization PSO Controller. It used to control for power electronic (inverter) &PMSM which worked in the integration system to PV energy. There are two parts in this paper, first part advanced Optimal PSO, Fuzzy &PI Controller power electronic (inverter) with PV for using different control systems this part on the generator side at constant torque. Second part in the load side of variable torque, by using different control systems with PMSM to analyze all results after using the simulation model of proposed based PV system. The PV system is coupled with PMSM. A closed loop control system with a PI control, Fuzzy, PSO in the speed loop with current controllers.